Empowering children to take control of their nutrition - Impact evaluation of the Nourishing Schools Initiative - Jani, B; Sinha, A; Adamo, G; Jani, A (2018)
Malnutrition is the most important risk factor for illness and death globally and is associated with more than one third of all deaths in young children. According to UNICEF, more than one third of the world's children who are wasted live in India and despite several efforts by the Government of India, the problem still persists. Ashoka Nourishing Schools utilises a six component toolkit that engages school-going children aged between 9-14 through their academic curriculum and community activities to create lifelong nutrition-seeking habits to prevent the vicious cycle of undernutrition. Ashoka Nourishing Schools and Lend-A-Hand India worked with 1016 children aged 9-14 from 14 schools across three districts (Pune, Sangli and Satara) in Maharashtra, India. The midline results of Nourishing schools include: a statistically significant reduction in the number of severely thin and thin children (100 at baseline to 23 post-intervention; 179 at baseline to 89 post-intervention, respectively); a statistically significant reduction in the number of severely anaemic children (68 at baseline to 9 post-intervention); a statistically significant reduction in goitre (11 at baseline to 3 post-intervention); and a statistically significant reduction in malaria (12 at baseline to 2 post-intervention). The promising results of Nourishing Schools demonstrate that working with schools to educate and empower children with knowledge about nutrition can lead to behavior change and positive health outcomes. It is hoped that these results can be expanded to other locations in India and globally where childhood malnutrition is a serious issue.